Peran Pemerintah Dalam Pembinaan Usaha Kecil Dan Menengah Menghadapi Revolusi Industri 4.0 Kota Pekanbaru - Sari, Nurma; Komalasari, Eka (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
Micro, Small, and Medium Enterprises are one of the pillars and drivers of the economy. This can be seen from the significant small business activities from both the traditional and modern sectors. This activity is one of the absorbers of labor and is the main pillar of economic growth in the development of a country. Problems in this activity are human resources who do not understand technology, limited marketing, technology is beyond the reach of business actors, and also does not allow investment in new technology. This study aims to analyze the role of the government in fostering small and medium enterprises to face the 4.0 industrial revolution in Pekanbaru city and to find out the government's obstacles in fostering small and medium enterprises facing the 4.0 industrial revolution in Pekanbaru city. The method used in this research is descriptive qualitative, collecting data by means of interviews, observations, and documentation with Small and Medium Enterprises and the Office of Cooperatives for Micro, Small, and Medium Enterprises. The results of the study indicate that the Government's Role in Fostering Small and Medium Enterprises to Face the Industrial Revolution 4.0 in Pekanbaru City seen from the indicators of facilitators, regulators, and catalysts can be concluded that it has been carried out quite well. There were several obstacles encountered, namely the lack of budget from the Regional Revenue and Expenditure Budget, the low mindset of Small and Medium Enterprises actors, and the lack of information received related to the guidance carried out.